Dimethyl 4-(3-hydroxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate - Rajesh, K.; Vijayakumar, V.; Narasimhamurthy, T.; Suresh, J.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The 1,4-dihydropyridine ring in the title compound, C(17)H(19)NO(5), has a flattened-boat conformation, and the benzene ring is almost orthogonal to it [dihedral angle = 82.98 (12)degrees]. The hydroxy group is disordered over two positions in a 0.780 (4): 0.220 (4) ratio. In the crystal, hydrogen-bonding interactions of the type N(a)-H center dot center dot center dot O(c) and O(h)-H center dot center dot center dot O(c) (a = amine, c = carbonyl and h = hydroxy) link the molecules into a three-dimensional network.